Epidemiology of Acute and Chronic Diseases in the Population of Preschool Children (Results of A Prospective Study) - Mamasoliev N.S; Otajonov I; Usmanov B.U; Kalandarov D.M (Zien Journals, 2023)
It is necessary to study and analyze the diseases of children of different age groups on the basis of improvement of medical and social assistance to children, improvement of effectiveness of preventive activities, and on the basis of these, measures aimed at maintaining and protecting children's health should be developed. In the study, diseases of preschool children were analyzed in depth, and their causes were studied. The obtained results showed that the incidence of children under seven years of age in Andijan depends on age, and the incidence rate decreases with age. In the structure of diseases, diseases of respiratory organs are leading at all ages. If the study of children's diseases under 7 years of age in the cities of Andijan region on the basis of appeals revealed the characteristics of children's diseases specific to this region, then the children who were not identified before the organization and conduct of medical examinations, without clinical symptoms, were registered in treatment-preventive institutions. allowed to identify new chronic diseases.
Keywords: Children; morbidity; children of preschool age; urban children